The Danger of Hoax: The Effect of Inaccurate Information on Semantic Memory - Arbiyah, Nurul; Adiningtyas, Dian; Widodo, Mitha; Safitri, Anisa (Makara Human Behavior Studies in Asia, 2020)
This study focuses on the vulnerability of general knowledge held in semantic memory. Previous studies have shown that exposure to inaccurate information can negatively affect prior knowledge. This study explores the effect of exposure to inaccurate information on semantic memory, presented in nonfiction articles. The procedure consisted of a pretest (general knowledge quiz), a manipulation stage one week later with articles containing inaccurate information for the experimental group and neutral information for the control group, and a posttest (another general knowledge quiz) given immediately after the manipulation stage. The participants were 55 Universitas Indonesia undergraduate students, divided into control and experimental groups by randomized matching based on the pretest results. An independent sample t-test showed a significant difference between the experimental group (M = −1.538, SD = 1.794) and the control group (M = 0.517, SD = 1.639), (t(53) = −4.441, p < 0.01, two-tailed), with the experimental group showing a decline in general knowledge quiz scores. These findings demonstrate that exposure to inaccurate information affects semantic memory by interfering with the retrieval process of that memory.